Making sense of Brexit: French skilled workers negotiating their migration, integration, and identification in the UK - Couloigner, Suzanne (2022)
After years of European expansion, the UK decided in 2016 to end its membership of the European Union (EU), now commonly known as Brexit. The present thesis contributes to the growing body of literature investigating the impacts of Brexit on EU citizens, with a specific focus on migration, integration, and identification. More specifically, the thesis builds on the idea that those three processes are interrelated, impacting one another, but are also ongoing, thus promoting the dynamic nature of migrating, integrating, and identifying. Furthermore, the thesis highlights how each process can be studied from a micro or macro perspective but that a connection between the two levels of analysis is rare. The thesis’ main objectives are thus (1) to explore individual migrants’ perceptions of the macro context in which migration, integration, and identification are negotiated, and (2) to investigate how a personal, migrant, idiosyncratic understanding of this context influences migrants’ migration, integration, and identification. To reach these two objectives, the thesis evolves around an overarching research question, namely, how do migrants’ perceptions of macro changes influence their migration, integration, and identification?